Assessing climate change impacts on hydrology: application to Zacapu and Pastor Ortiz aquifers (Mexico). Issue 5 (11th April 2022) - Flores-Fernández, Giovanni Carlo; García-Romero, Liliana; Sánchez-Quispe, Sonia Tatiana
Abstract: The agricultural and urban water requirements in the Angulo River basin (Mexico) along with land-use change and deforestation have caused great pressure on the region's groundwater availability. The potential climate change impact on groundwater levels of the Zacapu and Pastor Ortiz aquifers is evaluated in this study, using the climate model CMIP5, the hydrological module EVALHID, and the groundwater module AQUIVAL. The regional outputs from three Representative Concentration Pathway (RCP) climate scenarios (RCP 4.5, 6.0, and 8.5), for near future (2015–2039) and distant future (2075–2099) projections, indicate that the average annual temperature is expected to increase while a decrease in precipitation is projected over the basin. The assessment of infiltration and water level evolution in these groundwater systems indicates an infiltration reduction between 1.5 and 23%, producing a static level drop between 20 and 30 m in both aquifers. HIGHLIGHTS: A groundwater piezometry decrease is assessed as the RCP scenarios increase. The most considerable effects of temperature and precipitation data are related to winter and spring. The precipitation behavior is similar throughout the basin, with a small increase in the RCP 6.0 scenario. Graphical Abstract